2024
DOI: 10.3390/antiox13010124
|View full text |Cite
|
Sign up to set email alerts
|

The Hepatokine RBP4 Links Metabolic Diseases to Articular Inflammation

Andrés Pazos-Pérez,
María Piñeiro-Ramil,
Eloi Franco-Trepat
et al.

Abstract: Objectives: This study investigates the role of retinol binding protein 4 (RBP4) in an articular context. RBP4, a vitamin A transporter, is linked to various metabolic diseases. Methods: Synovial fluid RBP4 levels were assessed in crystalline arthritis (CA) patients using ELISA. RBP4’s impact on articular cell types was analysed in vitro through RT-PCR and flow cytometry. Proteomic analysis was conducted on primary human osteoarthritis chondrocytes (hOACs). Results: Synovial fluid RBP4 concentrations in CA pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(79 reference statements)
0
1
0
Order By: Relevance
“…Signaling pathways include signaling by GPCR [56] [99], EGFR (epidermal growth factor receptor) [100], ABCA1 [101], CRHR2 [102], RND3 [103], COMT (catechol-Omethyltransferase) [104] and SMAD9 [105] plays an important role in the pathogenesis of hypertension. Studies have revealed that NEUROD4 [106], SOX10 [107], MOG (myelin oligodendrocyte glycoprotein) [108], NR5A2 [109], GLRA3 [110], FA2H [111], SERPINA [112], HOXB9 [113], TGM2 [114], LRRK2 [115], ROS1 [116] NKX6-1 [141], SLC22A3 [142], CADM2 [143], FREM1 [144], TWIST2 [145], WNT16 [146], KISS1 [147], TMEM176B [148], MYL9 [149], IL7R [150], MBP (myelin basic protein) [151], GPR37 [152], ACAN (aggrecan) [153], SHH (sonic hedgehog signaling molecule) [154], HOXD9 [155], PROK1 [156], AGTR1 [157], TIE1 [158], P2RX7 [159], NTSR1 [160], VTN (vitronectin) [161], SIRT2 [162], RBP4 [163] [178], HLA-DRB1 [179], NKX2-3 [180], CD74 [92], HLA-DRA [181], VWF (von Willebrand factor) [182], BCL6B ...…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include signaling by GPCR [56] [99], EGFR (epidermal growth factor receptor) [100], ABCA1 [101], CRHR2 [102], RND3 [103], COMT (catechol-Omethyltransferase) [104] and SMAD9 [105] plays an important role in the pathogenesis of hypertension. Studies have revealed that NEUROD4 [106], SOX10 [107], MOG (myelin oligodendrocyte glycoprotein) [108], NR5A2 [109], GLRA3 [110], FA2H [111], SERPINA [112], HOXB9 [113], TGM2 [114], LRRK2 [115], ROS1 [116] NKX6-1 [141], SLC22A3 [142], CADM2 [143], FREM1 [144], TWIST2 [145], WNT16 [146], KISS1 [147], TMEM176B [148], MYL9 [149], IL7R [150], MBP (myelin basic protein) [151], GPR37 [152], ACAN (aggrecan) [153], SHH (sonic hedgehog signaling molecule) [154], HOXD9 [155], PROK1 [156], AGTR1 [157], TIE1 [158], P2RX7 [159], NTSR1 [160], VTN (vitronectin) [161], SIRT2 [162], RBP4 [163] [178], HLA-DRB1 [179], NKX2-3 [180], CD74 [92], HLA-DRA [181], VWF (von Willebrand factor) [182], BCL6B ...…”
Section: Discussionmentioning
confidence: 99%